การประยุกต์ใช้เทคนิคบัญชีต้นทุนการไหลของวัสดุและกำหนดการเชิงพลวัตในการปรับปรุงกิจกรรมห่วงโซ่อุปทานภายในสำหรับอุตสาหกรรมเฟอร์นิเจอร์ไม้ - อัจฉรา ทรงคำ (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
This study aimed to present an application of Material Flow Cost Accounting (MFCA) to discover loss in internal supply chain operations of the case study of one wooden furniture factory in Chiang Mai. The studied activities included purchasing, production and packaging and the results of MFCA were the cost of positive product as 25,128.77 or 46.97% and the cost of negative product as 28,367.05 or 53.03% of the total product cost. The cost of negative product was classified as material cost (MC) 45.52%, system cost (SC) 6.41%, and energy cost (EC) 1.10% of the total negative product cost. After that Pareto diagram and why-why analysis were used to find root causes of the cost of negative product. Motion and time study and ECRS concept were employed for developing improvement methods. Seven solutions were proposed for improving the studied process. Then, dynamic programming was applied for the best return solution and only 4 improvement solutions were selected. Then, 4 selected improvement solutions were implemented and evaluated again using MFCA calculation. The results showed that the cost of positive product was increased to 25,806.61 THB or 55.62% and the cost of negative product was reduced to 20,588.37 THB or 44.38%. The results from this improvement were affected on production cost reduction 7,100.84 THB (13.27%) per lot or 42,605.04 THB per year.